2010
DOI: 10.1063/1.3483462
|View full text |Cite
|
Sign up to set email alerts
|

Communication: The ionization and dissociation energies of HD

Abstract: The adiabatic ionization energy [in units of hc, [Ei=124 568.485 81(36) cm−1] and the dissociation energy [D0=36 405.783 66(36) cm−1] of HD have been determined using a hybrid experimental-theoretical method. Experimentally, the wave numbers of the EF(v=0,N=0)→np[X+(v+=0 and 1, N+=0)] and EF(v=0,N=1)→np[X+(v+=0,N+=1)] transitions to singlet Rydberg states were measured by laser spectroscopy and used to validate predictions of the electron binding energies by multichannel quantum defect theory. Adding the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 34 publications
4
70
1
Order By: Relevance
“…Similar to the case of atomic calculations and molecular BO calculations, a major advantage of the ECG method in the (Liu et al, 2009Drouin, 2011;Sprecher et al, 2010;Salumbides et al, 2011) and theoretically predicted (Piszczatowski et al, 2009;Pachucki and Komasa, 2010;Komasa et al, 2011) Koput (2011) reported the ground state energy of BeH of À15:246 593 a:u: (at the equilibrium internuclear distance and including the FCI and diagonal adiabatic corrections) and the fundamental vibrational frequency of 1987:68 cm À1 . These values were obtained at the multireference averaged coupled-pair functional (MR-ACPF) level of theory in conjunction with a septuple-zeta correlation-consistent valence basis set, augmented with sets of diffuse and tight functions (aug-cc-pCV7Z) basis.…”
Section: E Going Beyond the Born-oppenheimer Approximationmentioning
confidence: 99%
“…Similar to the case of atomic calculations and molecular BO calculations, a major advantage of the ECG method in the (Liu et al, 2009Drouin, 2011;Sprecher et al, 2010;Salumbides et al, 2011) and theoretically predicted (Piszczatowski et al, 2009;Pachucki and Komasa, 2010;Komasa et al, 2011) Koput (2011) reported the ground state energy of BeH of À15:246 593 a:u: (at the equilibrium internuclear distance and including the FCI and diagonal adiabatic corrections) and the fundamental vibrational frequency of 1987:68 cm À1 . These values were obtained at the multireference averaged coupled-pair functional (MR-ACPF) level of theory in conjunction with a septuple-zeta correlation-consistent valence basis set, augmented with sets of diffuse and tight functions (aug-cc-pCV7Z) basis.…”
Section: E Going Beyond the Born-oppenheimer Approximationmentioning
confidence: 99%
“…12), HD (Ref. 13), and D 2 (Ref. 14) have reached an accuracy of 11 MHz, 11 MHz, and 17 MHz, respectively ($0.0005 cm À1 ).…”
Section: Latest Measurements Of the Ionisation Energies Of Molecumentioning
confidence: 99%
“…12 The notation nlN + N is used to label Rydberg states throughout this article (all quantum numbers have their usual meanings, see, e.g., Table I 2 , although higher rovibrationally excited states can also be used for an extrapolation of the ionisation energies. 13 Because the relative energies of the lowest rotational levels of both neutral and ionised species are known with high accuracy, E i and D 0 can be derived from measurements of Rydberg series converging to excited rotational levels. In practice, Rydberg series converging to the lowest rotational levels (N + ¼ 0 and 1) are most convenient because autoionisation does not lead to undesirable line broadening.…”
Section: Latest Measurements Of the Ionisation Energies Of Molecumentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, full-fledged level structure calculations, including QED and high-order relativistic contributions have also been carried out for the neutral hydrogen molecules and the deuterated isotopomers [32][33][34]. These calculations have been tested in the determination of dissociation limits of H 2 [36], D 2 [37] and HD [38], as well as in measurements of the ground state rotational sequence of H 2 [39], and the vibrational splittings in H 2 , D 2 and HD [40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%